Using habitat suitability models in an industrial setting: the case for internesting flatback turtles - Paul A. Whittock; Kellie L. Pendoley; Mark Hamann (Ecosphere, 2016)
Abstract To predict and manage ecological impacts of anthropogenic activities effectively, an understanding of at‐risk species spatial ecology is first required. This is particularly difficult in the marine environment due to limited offshore access and wide‐ranging movements of some species. Flatback turtles are a protected species potentially at risk from hazards associated with the resource sector in Australia, yet their at‐sea spatial ecology is not well understood. We use habitat suitability modeling to identify environmental variables that influence flatback turtle internesting movement; identify areas of suitable internesting habitat; and determine overlap of identified internesting habitat with resource sector hazards. Internesting movements of 47 female flatback turtles, from five rookeries in the North West Shelf region of Western Australia, were recorded using platform terminal transmitters between 2006 and 2010. Environmental variables including sea surface temperature (SST), bathymetry, magnetic anomalies, distance from coastline, slope, and ruggedness index were combined with the tracking data from each rookery in an ecological niche model. We used the positions of resource sector vessels to represent areas of potential impact from resource sector hazards and identified overlap with suitable internesting habitat areas as a representative of the likelihood of impact. The primary environmental variables that influenced flatback internesting movement were bathymetry, distance from coastline, and SST. Suitable areas of internesting habitat were located in close proximity to many known flatback turtle rookeries across the region. Areas of suitable internesting habitat overlapped resource sector hazards in close proximity to four of the five rookeries and at other known flatback turtle rookeries. The cumulative overlap across the overall study area indicates a high potential for interaction with resource sector hazards, demonstrating the need for regional protection measures in these areas. This study provides a capability for regulators and developers to determine the potential offshore presence of internesting flatback turtles within the region, allowing for protection measures to be targeted appropriately as industrial development continues.